Fibrous materials - Chawla, Krishan Kumar 1942- (Cambridge solid state science series, 1998)
This book is about the processing, microstructure and properties of materials in fibrous form. The range of fibrous materials covered spans natural polymeric fibres such as silk, synthetic polymeric fibres such as aramid and polyethylene, metallic fibres such as steel and tungsten, and ceramic fibres such as alumina and silicon carbide. The author explains the fundamentals in a clear and concise manner and describes important advances in the production and control of microstructure in high stiffness and high strength fibres. The text contains large numbers of diagrams and micrographs to bring home to the reader the important principles and concepts. The book will be of value to senior undergraduates, beginning graduate students and researchers in the fields of materials science and engineering, metallurgy, ceramics, textile physics and engineering, mechanical engineering and chemical engineering